Spiritually Based Intervention to Increase Colorectal Cancer Screening Among African Americans: Screening and Theory-Based Outcomes From a Randomized Trial. (August 2013) - Holt, Cheryl L.; Litaker, Mark S.; Scarinci, Isabel C.; Debnam, Katrina J.; McDavid, Chastity; McNeal, Sandre F.; Eloubeidi, Mohamad A.; Crowther, Martha; Bolland, John; Martin, Michelle Y.
Colorectal cancer screening has clear benefits in terms of mortality reduction; however, it is still underutilized and especially among medically underserved populations, including African Americans, who also suffer a disproportionate colorectal cancer burden. This study consisted of a theory-driven (health belief model) spiritually based intervention aimed at increasing screening among African Americans through a community health advisor-led educational series in 16 churches. Using a randomized design, churches were assigned to receive either the spiritually based intervention or a nonspiritual comparison, which was the same in every way except that it did not contain spiritual/religious content and themes. Trained and certified peer community health advisors in each church led a series of two group educational sessions on colorectal cancer and screening. Study enrollees completed a baseline, 1-month, and 12-month follow-up survey at their churches. The interventions had significant pre–post impact on awareness of all four screening modalities, and self-report receipt of fecal occult blood test, flexible sigmoidoscopy, and colonoscopy. There were no significant study group differences in study outcomes, with the exception of fecal occult blood test utilization, whereas those in the nonspiritual intervention reported significantly greater pre–post change. Both of these community-engaged, theory-driven, culturally relevant approaches to increasing colorectal cancer awareness and screening appeared to have an impact on study outcomes. Although adding spiritual/religious themes to the intervention was appealing to the audience, it may not result in increased intervention efficacy.